Coexistence of dielectric relaxation and magnetic relaxation in compressively strained BiFeO3/Ba0.7Sr0.3TiO3 superlattices - Miao, Jun; Chew, Khian Hooi; Zhang, Lin Xing; Wu, Rui; Wang, Jia Ou; Shao, Fei; Zhan, Qian; Jiang, Yong (AIP Publishing, 2019)
Superlattices (SLs) consisting of multiferroic BiFeO3 (BFO) and dielectric Ba0.7Sr0.3TiO3 were epitaxially grown on a (001)-oriented Nb:SrTiO3 substrate using pulsed laser deposition. An improved ferroelectricity with a high-temperature polarization of ∼63.7 μC/cm2 at 470 K was observed. The SL exhibited both dielectric and magnetic relaxation properties. Two distinct dielectric relaxations were found: a carrier hopping process between Fe2+ and Fe3+ from 273 to 410 K and the long-range migration of oxygen vacancies from 430 to 573 K. Spin-glass behavior with a freezing temperature of ∼86.6 K was also observed. This work provides a promising path forward to tailor the multiferroic properties of BFO-based structures for high-temperature applications. © 2019 Author(s).